2020
DOI: 10.1080/13880209.2020.1743325
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of platelet-rich plasma (PRP) and a Sanguisorba officinalis polysaccharide on the proliferation and differentiation of anterior cruciate ligament (ACL) fibroblasts in vitro

Abstract: Context: Sanguisorba officinalis L. (Rosaceae), a famous traditional Chinese medicine. It was recently reported that its polysaccharide could facilitate collagen production. Objectives: We investigated the mechanism by which S. officinalis polysaccharide (SOWPa) and/or platelet-rich plasma (PRP) promote regenerative potential of anterior cruciate ligament (ACL) in vitro. Materials and methods: ACL fibroblasts were treated with SOWPa (25 and 100 mg/kg), PRP, PRP þ SOWPa (25 and 100 mg/kg) or vehicle alone for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A recent study has shown that miRNA-214-3p regulates the NF-κB signalling pathway by targeting IKBKB , and a decrease in miRNA-214-3p expression leads to an increase in IKBKB expression and activation of the NF-κB signalling pathway [ 28 ]. Another study has shown that platelet-rich plasma and Sanguisorba officinalis polysaccharide can increase the regenerative ability of ACL fibroblasts by blocking the TLR4/NF-κB pathway [ 35 ]. To clarify the expression pattern of IKBKB in the ACL, we compared IKBKB expression in normal and OA ACL cells and found that IKBKB was highly expressed in OA ACL cells but not in normal ACL cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that miRNA-214-3p regulates the NF-κB signalling pathway by targeting IKBKB , and a decrease in miRNA-214-3p expression leads to an increase in IKBKB expression and activation of the NF-κB signalling pathway [ 28 ]. Another study has shown that platelet-rich plasma and Sanguisorba officinalis polysaccharide can increase the regenerative ability of ACL fibroblasts by blocking the TLR4/NF-κB pathway [ 35 ]. To clarify the expression pattern of IKBKB in the ACL, we compared IKBKB expression in normal and OA ACL cells and found that IKBKB was highly expressed in OA ACL cells but not in normal ACL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al. [ 31 ] found that PRP could improve the migration abilities of ACL fibroblasts significantly, especially at 72 ​h after cell seeded. The growth factors like TGF-β and FGF, as the component of PRP, have been proved to stimulate cell growth and migration [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRP has also been used as a vessel for therapeutic delivery of bioactive agents or cells. For example, Zheng et al (2020) examined the effects of PRP and a Sanguisorba officinalis polysaccharide (SOWPa), a Chinese herb known to enhance collagen deposition, on ACL fibroblasts. Another common PRP administration approach includes the addition of adipose‐derived progenitor cells (ADPCs) or mesenchymal stem cells (MSCs) (often in the form of bone marrow aspirate concentrate [BMAC]).…”
Section: Prp/prfmentioning
confidence: 99%